Development and Structural Evaluation of Dog Bone Particle–Reinforced Epoxy Composites for Biomedical Applications - Adebayo Felix Owa; Peter Apata Olubambi (Advances in Materials Science and Engineering)
There has been great interest in developing high-performance, sustainable and eco-friendly materials. This study presents an innovative development and research of the mechanical properties of dog bone–reinforced epoxy composites to determine their suitability for biomedical applications. Good surface compatibility for the matrix and reinforcement was the target, complementing the structural compatibility needed for such applications. Hand-lay open mould technique was used to fabricate the composites with varying weight percentage of dog bone particles (DBPs), and mechanical properties (tensile strength, Young’s modulus, percentage elongation and flexural strength) were determined. The results show that the developed composites’ mechanical properties were enhanced, and the tensile strength of 21.10 MPa–27.97 MPa, Young’s modulus of 1531.00 MPa–1732.90 MPa, ductility of 2.10%–2.60% and flexural strength of 27.53 MPa–35.67 MPa were recorded for the biocomposites. Energy-dispersive X-ray spectroscopy (EDS) revealed the main elements’ contents of the DBPs as calcium (50.3%), carbon (20.77%) and oxygen (11.76%). Scanning electron microscopy (SEM) examination of the fractured surfaces revealed the homogeneous distribution of the dog bone particulates within the epoxy matrix, which caused the property enhancement. The findings of this research underline the potency of processed animal waste as filler materials.